PENGARUH KUALITAS AUDIT, PERGANTIAN AUDITOR, DAN KOMPLEKSITAS OPERASI PERUSAHAAN TERHADAP AUDIT REPORT LAG DENGAN BOARD GENDER DIVERSITY SEBAGAI VARIABEL MODERASI - Fakhriyah, Ananda Laili; Bawono, Andy Dwi Bayu (ITB AAS Indonesia Surakarta, 2024)
The objective of this study is to examine the impact of audit quality, auditor turnover, and operational complexity on the duration of audit reports, with a particular focus on the moderating role of board gender diversity. The research conducted is quantitative in nature and utilizes secondary data. The population under study consists of manufacturing companies that were listed on the IDX between 2019 and 2021. The data collection process employed a purposive sampling technique, utilizing annual financial report data obtained from either the IDX or the company's website. The overall sample size consisted of 276 individuals. The research employed multiple regression analysis and MRA utilizing SPS version 25.0 as the data analysis approach. The findings derived from the conducted tests indicate that there is no significant impact of auditor changes and the complexity of firm operations on audit report lag. However, it is observed that audit quality has a detrimental effect on audit report lag. The moderating effect of board gender diversity on the relationship between audit quality, auditor turnover, and the complexity of firm operations on audit report lag is found to be ineffective Keywords : audit quality, auditor changes, complexity of firm operations, audit report lag, board gender diversity